Co-operative land use, the challenge to traditional co-operation - Digby, Margaret (Oxford : Blackwell, 1963)
This book reveals challenges to traditional co-operation in western Europe, Australia and America
oo 17/01/2019
Loans
Keywords: Agriculture, Cooperative; Collective farms